The equation of the entropy production in a tribounit - Ventsel, Ye.; Shchukin, O.; Orel, O.; Saienko, N. (Problems of Tribology, 2020)
It is proposed to consider the tribounit as a non-equilibrium thermodynamic system in which entropy is produced. The corresponding equation is obtained, whose analysis shows that in order to bring the tribounit to a stationary state, in which the entropy production tends to zero, and there is a minimum of friction force and a wear rate, it is necessary to reduce the coefficient of dynamic viscosity of the lubricating medium, the speed of relative motion of tribo-surfaces, sizes of contaminant particles, etc. As a result of laboratory studies, it has been established, in particular, that the presence of contaminant particles in the oil with the average weighted size of 10.36 μm leads to a decrease in the oil temperature, the friction coefficient and wear of the tribo-surfaces compared to the oil in which the average weighted size of particles is 35.8 μm. This proves the original hypothesis of the article that the tribounit is a thermodynamic system in which entropy is produced, and to which the laws of non-equilibrium thermodynamics are applicable